2007
DOI: 10.2224/sbp.2007.35.5.627
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Stage Model of Volunteers' Duration of Service

Abstract: The main objective of this paper was to describe the latest results of a longitudinal study carried out by our research team with a sample of social work volunteers, whose one-year follow-up has just been completed, allowing us to draw up what we have called the "Threestage model of volunteers' duration". Use of this model overcomes some of the apparent contradictions between the different models of volunteerism. For example, for the Functional Model, motivations, and more specifically their satisfaction, woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
180
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(202 citation statements)
references
References 30 publications
14
180
1
7
Order By: Relevance
“…The findings of this study extend our understanding of volunteer legacies emphasizing that like other legacies, volunteer legacies may emerge organically, without planned and coordinated efforts of the event organizers, and can create a sustained change in attitudes and behavior of those who volunteer at these events. This study also expands on the work of Doherty (2009), who suggests that satisfied volunteers will likely volunteer in the future, as well as on the work of role identity theorists (Callero et al, 1987;Chacón et al, 2007;Finkelstein, 2009;Grube & Piliavin, 2000;Jiménez et al, 2010;Piliavin et al, 2002;Van Dyne & Farmer, 2005) who Thus, the group used the event itself to introduce a younger generation into the role of volunteering.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The findings of this study extend our understanding of volunteer legacies emphasizing that like other legacies, volunteer legacies may emerge organically, without planned and coordinated efforts of the event organizers, and can create a sustained change in attitudes and behavior of those who volunteer at these events. This study also expands on the work of Doherty (2009), who suggests that satisfied volunteers will likely volunteer in the future, as well as on the work of role identity theorists (Callero et al, 1987;Chacón et al, 2007;Finkelstein, 2009;Grube & Piliavin, 2000;Jiménez et al, 2010;Piliavin et al, 2002;Van Dyne & Farmer, 2005) who Thus, the group used the event itself to introduce a younger generation into the role of volunteering.…”
Section: Discussionmentioning
confidence: 88%
“…It has been suggested that a key causal mechanism that strengthens the likelihood of repeat volunteering behavior is the development of a volunteer role identity (Callero, Howard, & Piliavin, 1987;Chacón, Vecina, & Dávila, 2007;Jiménez et al, 2010;Van Dyne & Farmer, 2005). Role identity theory predicts that over time the volunteer role an individual undertakes becomes incorporated into that individual's self-concept (Van Dyne & Farmer, 2005).…”
Section: The Spirit Lives On: the Legacy Of Volunteering At The Sydnementioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies and longitudinal studies are needed to further test whether volunteering improves the physical and psychological well-being among volunteers of different age through satisfying their goals. In particular, studies on sustained volunteerism revealed that the endorsement of volunteering motives only predicted volunteering experience at the beginning but not for longer periods (Chacon et al 2007;Finkelstein 2006;Finkelstein et al 2005). Future studies should further examine the well-being benefits of volunteering motives in longitudinal studies to disentangle the short-term and long-term effects of volunteering motives among different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Starnes & Wymer (2001) points out that people continue volunteering their services when they experience job satisfaction such as finding it is interesting and challenging, experiencing new learning opportunities, allowing for independence and achieving personal or professional growth. A study among social work volunteers also found that satisfaction would be the best predictors of service duration (Chacon & Vecina, 2007).…”
Section: Introductionmentioning
confidence: 99%